Development potentials of the Subcarpathian Voivodeship – diagnosis and assessment - Bański, Jerzy; Czapiewski, Konrad Ł.; Mazur, Marcin (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2015)
The purpose of this article is to assess the development potential of the Subcarpathian Voivodeship in relation to other regions of the country (divided into five categories of potential: demographic and social, natural and cultural, economic, spatial and institutional) indicating the main determinants and barriers of development and the identification of the key sectors of the economy of the region. The basic research question is: Which sectors of the economy in Subcarpathian Region may contribute to its competitive advantage over other regions in the country? During the study a broad range of social (including in-depth interviews and focus group interviews with entrepreneurships, representatives of local government and non-governmental organizations) and statistical methods were used, which allowed to accumulate a vast collection of empirical materials. Based on the research, it was found that the economic and socio-demographic potential plays the key role in the region.